2021
DOI: 10.1371/journal.pone.0260663
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and reliability of TMS-evoked short- and long-latency afferent interactions

Abstract: Short-latency afferent inhibition (SAI) and long-latency afferent inhibition (LAI) occur when the motor evoked potential (MEP) elicited by transcranial magnetic stimulation (TMS) is reduced by the delivery of a preceding peripheral nerve stimulus. The intra-individual variability in SAI and LAI is considerable, and the influence of sample demographics (e.g., age and biological sex) and testing context (e.g., time of day) is not clear. There are also no established normative values for these measures, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Given that ICC values are a function of the between-subject variability in a sample, with large amounts of between-subject variability leading to higher estimates of relative reliability, this likely explains the trends in reliability seen across the literature and in the present study ( Bruton et al, 2000 , Weir, 2005 ). We recently published a large retrospective analysis of SAI and LAI data which also showed larger amounts of between-subject variability for LAI compared to SAI, with a plausible reasoning being the different neurological pathway that LAI may traverse ( Toepp et al, 2021 ). We theorize that because LAI is evoked at longer ISIs, there is possible activation of additional brain regions including the basal-ganglio-thalamocortical loop, the posterior parietal cortex, and the secondary somatosensory cortex ( Toepp et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that ICC values are a function of the between-subject variability in a sample, with large amounts of between-subject variability leading to higher estimates of relative reliability, this likely explains the trends in reliability seen across the literature and in the present study ( Bruton et al, 2000 , Weir, 2005 ). We recently published a large retrospective analysis of SAI and LAI data which also showed larger amounts of between-subject variability for LAI compared to SAI, with a plausible reasoning being the different neurological pathway that LAI may traverse ( Toepp et al, 2021 ). We theorize that because LAI is evoked at longer ISIs, there is possible activation of additional brain regions including the basal-ganglio-thalamocortical loop, the posterior parietal cortex, and the secondary somatosensory cortex ( Toepp et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We recently published a large retrospective analysis of SAI and LAI data which also showed larger amounts of between-subject variability for LAI compared to SAI, with a plausible reasoning being the different neurological pathway that LAI may traverse ( Toepp et al, 2021 ). We theorize that because LAI is evoked at longer ISIs, there is possible activation of additional brain regions including the basal-ganglio-thalamocortical loop, the posterior parietal cortex, and the secondary somatosensory cortex ( Toepp et al, 2021 ). The potential activation of these various regions introduces several avenues of variability between individuals, which is not seen in SAI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MEPs and resting motor threshold have demonstrated good test re-test reliability in contrast to measures of intracortical facilitation [ 36 ]. Researchers have also explored the reliability of afferent inhibition and concluded that SAI and LAI demonstrate poor to moderate reliability [ 37 , 38 ]. The relative reliability of afferent inhibition measures across studies also seem to vary substantially, indicating that there may be methodological factors including coil placement, electrode placement [ 39 ] that are modulating reliability [ 40 ].…”
Section: Introductionmentioning
confidence: 99%